1990
DOI: 10.1080/15287399009531416
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relationship of ozone‐induced airway hyperresponsiveness in unanesthetized guinea pigs

Abstract: The effect of ozone dose (the product of ozone concentration and exposure time) on airway responsiveness was examined in unanesthetized, spontaneously breathing guinea pigs. Airway responsiveness was assessed by measuring specific airway resistance (sRaw) as a function of increasing concentration of inhaled methacholine (Mch) aerosol (the concentration of Mch required in order to double the baseline sRaw: PC200Mch). The airway responsiveness was measured before and at 5 min, 5 h, and 24 h after exposure. A 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…It has been well documented that airway hyperresponsiveness is experimentally induced by a single exposure to noxious gas including ozone and cigarette smoke [7,15,16,22,24,25,28]. These experimental models differ from clinical asthma in that alterations in airway responsiveness are usually transient and resolve completely in a period of hours to days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been well documented that airway hyperresponsiveness is experimentally induced by a single exposure to noxious gas including ozone and cigarette smoke [7,15,16,22,24,25,28]. These experimental models differ from clinical asthma in that alterations in airway responsiveness are usually transient and resolve completely in a period of hours to days.…”
Section: Discussionmentioning
confidence: 99%
“…4A,B,D,E). Our previous data in guinea pigs showed no significant correlation between the changes in baseline sRaw and the increase in airway responsiveness after ozone exposure [24]. Several human studies have shown that brief exposure to ozone causes changes in airway hyperresponsivehess in the absence of changes in pulmonary mechanics [10,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased responsiveness is usually demonstrated through pharmacological methods, i.e., the elaboration of dose-response curves with bronchoconstrictor agents. In laboratory animals, the most common ways to deliver these agents to the airways are the intravenous (22,23) and the inhalatory routes (14,17). Although extensively used to demonstrate this phenomenon, differences between inhaled and intravenously admin-istered agents have been very scantily investigated (18).…”
mentioning
confidence: 99%